Contemporary Curriculum in Christian Religious Education - Kristiani Yanti Kana (Indonesian Journal of Christian Education and Theology, 2026)
The curriculum in Christian Religious Education (PAK) continues to develop along with the dynamics of the times, technological advancements, and changes in the characteristics of students. This article aims to examine in depth the concept of contemporary curriculum in PAK, including its main characteristics, theological foundations, and relevance in shaping the faith and character of students in the modern era. This research uses a qualitative approach through literature study by analyzing various theological, pedagogical, and educational policy sources of the latest education. The results of the study show that the contemporary curriculum of PAK has the main characteristics of a student-centered approach, contextual, integrative between faith and life, and utilizing technology as a learning medium. In addition, this curriculum emphasizes transformational aspects, namely changes in attitudes, values, and behaviors that reflect Christian teachings in daily life.